Genetic variation of the transthyretin gene in wild-type transthyretin amyloidosis (ATTRwt) - Sikora, Jacquelyn L. (Hum Genet, 2014)
Wild-type transthyretin amyloidosis (ATTRwt), typically diagnosed as congestive heart failure in elderly Caucasian men, features myocardial amyloid deposits of wild-type plasma protein transthyretin (TTR). ATTRwt is sporadic, its pathogenesis is poorly understood, and currently there are no biomarkers for diagnosis or prognosis. Genetic studies of variant-associated transthyretin amyloidosis (ATTRm) have suggested that non-coding TTR gene variants modulate disease. We hypothesized that cis-acting regulatory elements in the TTR gene non-coding regions may modify expression, affecting ATTRwt onset and progression. We studied an ATTRwt cohort consisting of 108 Caucasian males ranging in age from 59–87 years with cardiomyopathy due to wild-type TTR deposition; results were compared to 118 anonymous controls matched by age, sex, and race. Four predicted non-coding regulatory regions and all exons in the TTR gene were sequenced using the Sanger method. Eleven common variants were identified; 3 variants were significantly associated with ATTRwt (p < 0.05), though only one, rs72922940, remained near significance (p(corrected) = 0.083) after multiple testing correction. Exon analyses demonstrated the occurrence of the p.G26S (G6S) polymorphism in 7% of ATTRwt subjects and 12% of controls; this variant was predicted to be a protective factor (p = 0.051). Four variants were significantly associated with age at onset and survival. In this first genetic study of a large, well-characterized cohort of ATTRwt, non-coding and coding variants associated with disease, age at onset, and survival were identified. Further investigation is warranted to determine the prevalence of these variants in ATTRwt, their regulatory function, and potential role in assessing disease risk.